2017
DOI: 10.4067/s0719-81322017000200071
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimation to milk yield and fat and protein yield deviated from 3% of concentration in milk, in dairy herds of southern Chile

Abstract: ABSTRACT. Chilean milk processing industry is providing clear signs to milk farmers regarding the significant importance of milk solids within raw milk payment schemes. A litre of milk containing 3% of fat and 3% of protein is defined as a basic litre and, each additional kilo of fat and/or protein receives an extra payment. These are new production traits which must be researched on. In this study, 64,029 lactations, on 24 Región de Los Ríos at Southern of Chile herds, were used. Genetic parameters for milk y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…This is very similar to that reported by García et al (2001) (0.24 ± 0.001), who used a subset of the data included in this study. This estimate (0.26 ± 0.011) is higher than that reported in two studies on Chilean dairy cows conducted by Uribe et al (2017) and Montaldo et al (2015), who reported values of 0.16 ± 0.004 and 0.19 ± 0.006, respectively. Uribe and Smulders (2004) found that heritability estimate for milk yield in Chilean Overo Colorado cattle was 0.25, which is similar to that found in this study (Table 3).…”
Section: Heritabilitycontrasting
confidence: 60%
See 1 more Smart Citation
“…This is very similar to that reported by García et al (2001) (0.24 ± 0.001), who used a subset of the data included in this study. This estimate (0.26 ± 0.011) is higher than that reported in two studies on Chilean dairy cows conducted by Uribe et al (2017) and Montaldo et al (2015), who reported values of 0.16 ± 0.004 and 0.19 ± 0.006, respectively. Uribe and Smulders (2004) found that heritability estimate for milk yield in Chilean Overo Colorado cattle was 0.25, which is similar to that found in this study (Table 3).…”
Section: Heritabilitycontrasting
confidence: 60%
“…The milk yield mean was (4,432 ± 1,224 (Table1), and it is much lower than that reported by Elzo et al (2004) and Uribe et al (2017). They reported values of 7,502 ± 1,829 and 7,606 ± 1,670, respectively, adjusted to a 305-days mature equivalent.…”
Section: Phenotypic Parametersmentioning
confidence: 66%
“…The fieldwork has been conducted from November 2018 till January 2019 in three regions of Chile: Araucanía, Los Ríos, and Los Lagos, where 76% of all dairy milk in Chile is produced (Gonzalez & Katial, 2016;Uribe et al, 2017). The city of Valdivia is a central point of work, and it is 850 km to the south of Santiago, the capital of Chile.…”
Section: The Sector Of Studymentioning
confidence: 99%
“…In 2016, Chilean milk production reached 1.99 billion liters. Moreover, the economic success of a farmer in Chile is continuously more focused on milk solids output per unit of land rather than milk yield per cow (Uribe et al, 2017).…”
Section: The Sector Of Studymentioning
confidence: 99%
“…Some attempts have been made to estimate the genetic parameters of the Chilean Holstein population but none of them has used RRMs (Elzo et al 2004, Montaldo et al 2017, Uribe et al 2017. The objective of this study was to estimate genetic parameters such as heritability (h 2 ) and repeatability (rep) for daily milk yield, using orthogonal polynomials in a random regression test-day model in cows of Los Ríos Region, Chile.…”
Section: Introductionmentioning
confidence: 99%